Aktor Lokal, Industri Rekaman Musik, dan Musik Daerah: Peran dan Kontribusi Hila Hambala pada Gitar dan Gambus Tunggal Lampung Pesisir - Ricky Irawan (Institut Seni Indonesia Denpasar, 2022)
Purpose: This article aims to examine the progress of music recording technology in cassette form and the role of local actors, encouraging the development and giving shape to the toponymy of Lampung regional music today. Research Method: through a diachronic perspective, the author focuses on Hila Hambala, a musician, composer of Lampung-language songs, who is also widely known as an important figure in the development of guitar and gambus tunggal Lampung Pesisir, and Lampung dangdut. Several issues will be discussed, including: the learning process, the music environment, and Hila Hambala's involvement in music recording (in Jakarta and Lampung) since the early 80's which resulted in recordings of her works in the form of audiocassettes and video compact discs. Results and Discussion: Hila Hambala's involvement since the 80s in regional music and popular music from the Lampung region has not only boosted the popularity of his name and works, but in turn has also helped to define and shape the landscape of local music in Lampung, namely guitar and gambus tunggal of coastal Lampung. Implication: This research contributes to the discourse on the role and implications of modernity through advances in music recording technology having an impact on regional music.